2022
DOI: 10.1177/17590914221100706
|View full text |Cite
|
Sign up to set email alerts
|

Neural Functions of Hypothalamic Oxytocin and its Regulation

Abstract: Oxytocin (OT), a nonapeptide, has a variety of functions. Despite extensive studies on OT over past decades, our understanding of its neural functions and their regulation remains incomplete. OT is mainly produced in OT neurons in the supraoptic nucleus (SON), paraventricular nucleus (PVN) and accessory nuclei between the SON and PVN. OT exerts neuromodulatory effects in the brain and spinal cord. While magnocellular OT neurons in the SON and PVN mainly innervate the pituitary and forebrain regions, and parvoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 307 publications
(432 reference statements)
3
34
0
1
Order By: Relevance
“…This is in accord with the conserved mammalian neuroanatomy of central OT release, in which hypothalamic nuclei, particularly the synthesize OT and stimulate its release in the brain (9)(10)(11)(12)(13)(14). In rats, stroking touch increases Fos protein expression in PVN (52), and recent evidence from freely-interacting female rats indicates that a population of parvocellular OT neurons in PVN is selectively tuned to social touch stimulation (1,13). In the present study, BOLD changes in dorsal raphe nuclei also covaried…”
Section: Bold Correlates Of Endogenous Ot Changessupporting
confidence: 88%
See 1 more Smart Citation
“…This is in accord with the conserved mammalian neuroanatomy of central OT release, in which hypothalamic nuclei, particularly the synthesize OT and stimulate its release in the brain (9)(10)(11)(12)(13)(14). In rats, stroking touch increases Fos protein expression in PVN (52), and recent evidence from freely-interacting female rats indicates that a population of parvocellular OT neurons in PVN is selectively tuned to social touch stimulation (1,13). In the present study, BOLD changes in dorsal raphe nuclei also covaried…”
Section: Bold Correlates Of Endogenous Ot Changessupporting
confidence: 88%
“…It is wellestablished that magnocellular oxytocin neurons in the paraventricular nucleus (PVN) of the hypothalamus send projections to forebrain and cortical regions mediating olfactory and somatosensory signaling in the brain (9)(10)(11)(12). For tactile stimulation, this signaling may rely on a recently-discovered population of parvocellular OT neurons in the rat PVN selective for particular forms of affiliative touch (1,13,14). OT released into the bloodstream via a PVNpituitary pathway modulates the action of vasculature and smooth muscle (15), notably during processes surrounding reproductive behavior in both sexes, as well as parturition and lactation in females (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Both of these areas are also enriched with OxtRs in rodents ( Barberis and Tribollet, 1996 ). There are several reviews that explain the cardiovascular control of Oxt in detail ( Gutkowska and Jankowski, 2012 ; Jankowski et al, 2020 ; Szczepanska-Sadowska et al, 2021 ; Wang et al, 2022 ).…”
Section: Oxytocin Regulation Of Somatic/visceral Controlmentioning
confidence: 99%
“…Oxytocin (Oxt) was originally identified in 1906 as the primary molecule involved in parturition and lactation ( Dale, 1906 ). Further studies over the past centenary identified this nonapeptide’s role in regulating multiple other behaviors both in the central and peripheral nervous systems ( Lee et al, 2009 ; Jurek and Neumann, 2018 ; Lefevre et al, 2021 ; Wang et al, 2022 ). As further studies elucidate this molecule’s impact on brain and body systems, efforts to explore and establish the brain circuit level mechanisms of Oxt’s functional control have proliferated.…”
Section: Introductionmentioning
confidence: 99%
“…The peripherally secreted oxytocin acts into the uterine smooth muscle cells [ 14 ] and into the muscle-like cells (myoepithelial cells) into the breast [ 15 , 16 ] ( Figure 1 a). Along with the magnocellular PVN cells producing oxytocin, parvocellular and the accessory nuclei cells from the PVN also produce oxytocin [ 17 ]. Another hormone, the antidiuretic hormone (ADH; shaded circle in Figure 1 a) [ 18 ], is produced by the same nuclei in the PVN as oxytocin [ 19 ] and shares similar, but also different, actions with it.…”
Section: Introductionmentioning
confidence: 99%